Detection of Helicobacter pylori in recurrent aphthous ulceration by nested PCR. - Iamaroon A. (2014)
Recurrent aphthous ulceration (RAU) is the most common lesion of the oral mucosa. Although many factors have been postulated as etiological factors for RAU, the role of Helicobacter pylori as a causative agent of RAU remains controversial. We therefore investigated the association of H. pylori and RAU by a highly sensitive technique, nested polymerase chain reaction (PCR), in 22 patients with RAU with ages ranging from 12-36 years. Samples were brushed from the lesions and the dorsum of the tongue of each patient. In addition, samples from the dorsum of the tongue of 15 normal individuals with ages ranging from 13-40 years were used as controls. The results showed that only one sample from a lesion (4.5%) and one sample from the tongue (4.5%) of two different patients with RAU were positive for H. pylori. In the control group, 3 samples (20%) were positive for H. pylori. These findings suggest that H. pylori does not play a role in the pathogenesis of RAU and the dorsum of the tongue may be a reservoir of H. pylori in some individuals.